N‐Alkanes and PAHs in the Southeastern Tibetan Plateau: Characteristics and Correlations With Brown Carbon Light Absorption. Issue 19 (26th September 2020) - Zhu, Chong‐Shu; Li, Li‐Juan; Huang, Hong; Dai, Wen‐Ting; Lei, Ya‐Li; Qu, Yao; Huang, Ru‐Jin; Wang, Qi‐Yuan; Shen, Zhen‐Xing; Cao, Jun‐Ji
Abstract: The samples of atmospheric total suspended particle (TSP) were obtained at the remote Tibetan site (named Lulang) from November 2015 to November 2016. The seasonal characteristics of n ‐alkanes, polycyclic aromatic hydrocarbons (PAHs) variations, and their correlations to brown carbon (BrC) light absorption in TSP were investigated. Elevated TSP n ‐alkanes and PAHs levels were observed in winter (2.8 and 10 times higher than in monsoon, respectively), largely due to the seasonal contributions of wintertime home heating and long‐range transport. The total‐PAHs was found to correlate strongly with the methanol‐soluble BrC (MeS‐BrC) light absorption coefficient ( b abs ) ( R  = 0.80) compared to water‐soluble BrC (WS‐BrC) ( R  = 0.70) at 365 nm. The BrC solar absorptions percentages to those of element carbon (EC) in the range of ultraviolet (300–400 nm) were high in both winter and premonsoon seasons, which can affect the vulnerable environmental radiative balance and atmospheric photochemistry. Key Points: The seasonal characteristics of n ‐alkanes and polycyclic aromatic hydrocarbons were investigated The total‐PAHs were found to correlate strongly with the light absorption coefficient of MeS‐BrC compared to WS‐BrC at 365 nm The fractional solar absorptions by BrC relative to EC in the ultraviolet range were significant in winter and premonsoon seasons